Etnomatemática: An empirical field for study analysis of a Scientific Event (Research, Society and Development, 2019)
The present study presents an analysis of the works - published in the Annals from 2012 to 2018 of the event Winter School of Mathematics Education, National Meeting PIBID - Mathematics and Gaucho Meeting of Mathematics Education - related to Ethnomathematics. The research had twelve productions during this period, selected through the word Ethnomathematics in titles or keywords. In this way, it is possible to infer that, in addition to being vast, the field of Ethnomathematics makes possible different approaches, involving school and non-school contexts. The analysis also allowed to infer that the totality of works presented directly refers to the theoretical-methodological assumptions related to D'Ambrosio's ideas.